Effectiveness of the QARR Strategy to Enhance Thai EFL Students' Performance in Reading Comprehension Test - Yathip, Chatchanan; Liang-Itsara, Aphiwit (LEARN Journal: Language Education and Acquisition Research Network, 2024)
The Question-Answer-Relationship (QAR) strategy has been suggested to improve EFL students' reading comprehension. Nonetheless, disappointing outcomes when using the QAR instruction were noted. The current study seeks to 1) add the Review (R) component to the instruction and 2) assess the effectiveness of the developed Question-Answer-Response-Review (QARR) instruction to improve reading comprehension among Thai EFL university students. Instructional concepts such as common question types (Yathip & Chanyoo, 2022), the Question-Answer-Relationship strategy (Raphael & Au, 2005), the experiential learning approach (Kolb, 2014), and the reading instruction principle (Raphael, Highfield, & Au, 2006) were synthesized to create the instruction. The developed curriculum was implemented with 58 Thai EFL students. Data were examined using frequency, mean, standard deviation, and F-test. As for the findings, the experts' high degree of agreement (M = 0.96) demonstrated the efficiency of the developed instruction. One-way repeated measures revealed that the posttest (M = 21.74, SD = 4.12, d = 0.89) and delayed posttest (M = 22.19, SD = 4.23, d = 0.95) were substantially higher than the pretest mean scores (M = 16.86, SD = 5.59, p <.001) with a large effect size (η2= 0.209). Participants' satisfaction surveys strongly agreed with the created instruction (M = 4.36, SD = 0.63), consistent with interview data.